The role of a song in a Hindi film (The South Asianist Journal, 2013)
The article explores the role of the ‘Film Song’ in the life and popularity of a Hindi film and study its unique narrative attributes and purpose vis-à-vis songs in other world cinemas. The Hindi film song has been an integral and integrated part of a Hindi film’s script. It not only exists in a musical Hindi movie but is also used as a narrative device in films of every genre from comedies and romances to crime thrillers and horror films, most of which, routinely, may have five or more songs. The lyrics of songs are used to convey progressions in sequence and character moods much more succinctly than volumes of dialogues and visual sequences, accompanied by vocal music backed by an appropriate orchestral tenor in both popular and art-house Hindi movies. Though this may seem unreal to a viewer from another culture, it is not so for the traditional Hindi film audience as the format and presence of a song in a celluloid narrative traces its roots to ancient Indian folk theatre (called Nautanki) and age-old storytelling traditions. This article, while providing a historical perspective to the origin of the Hindi film song, introduces readers to some of the legends of Hindi cinema’s music-making industry that enjoys an independent life of its own, often beyond its source films’ run and popularity. Moreover, it explains the role of the primary collaborators involved in the making of a Hindi film song, and discuss the structure, functions and integral narrative duties of a good film song for a fair appraisal of its existence. Standout examples of songs from the 84-year-old journey of the Hindi film song are used to argue why it should be appreciated as one of the most crucial forms of Indian popular culture.